Particle number-based trophic transfer of gold nanomaterials in an aquatic food chain - Abdolahpur Monikh, Fazel; Chupani, Latifeh; Arenas-Lago, Daniel; Guo, Zhiling; Zhang, Peng; Darbha, Gopala Krishna; Valsami-Jones, Eugenia; Lynch, Iseult; Vijver, Martina G.; van Bodegom, Peter M.; Peijnenburg, Willie J.G.M. (Nature communications, 2021)
Analytical limitations considerably hinder our understanding of the impacts of the physicochemical properties of nanomaterials (NMs) on their biological fate in organisms. Here, using a fit-for-purpose analytical workflow, including dosing and emerging analytical techniques, NMs present in organisms are characterized and quantified across an aquatic food chain. The size and shape of gold (Au)-NMs are shown to control the number of Au-NMs attached to algae that were exposed to an equal initial concentration of 2.9 × 10 11 particles mL −1 . The Au-NMs undergo size/shape-dependent dissolution and agglomeration in the gut of the daphnids, which determines the size distribution of the NMs accumulated in fish. The biodistribution of NMs in fish tissues (intestine, liver, gills, and brain) also depends on NM size and shape, although the highest particle numbers per unit of mass are almost always present in the fish brain. The findings emphasize the importance of physicochemical properties of metallic NMs in their biotransformations and tropic transfers. Biological fate of nanomaterials in organisms is an important topic, however, limitations of analytical techniques has hampered understanding. Here, the authors report on a study into the fate of model, gold nanoparticles in an aquatic food chain using an analytical workflow and range of analytical methods.